La incidencia de la música en el proceso de aprendizaje en los niños con Síndrome de Down - Fernández Orozco, Paola Estefanía (2024)
The present research project focuses on the impact of music on the learning process in Down syndrome as a strategy to improve the comprehensive development of students. The objective of the present study includes determining the educational contribution of music for the learning process in the fourth grade girl of the “Mulaló” Educative Unity located in Cotopaxi Province, Latacunga-Mulaló Parish, school year 2023 – 2024. A methodology based on the qualitative approach with the inductive method was applied. along with the empirical method and the case study method, through observation. The sample was specifically made up of a student from the “Mulaló” Educative Unity, a student who was taken as a sample for the investigation. The techniques used were interview and observation using as an instrument an observation guide for the student in class and an interview guide for the mother, allowing the necessary information for her history life to be obtained. In conclusion, it was evident that the most relevant problems that the student with Down syndrome presents is the difficulty of socializing, communicating and also learning. Finally, the girl’s life story with Down syndrome was made, in order to raise awareness among other people who deal with children with Down syndrome and thus include them in society.